ON THE PECULIARITIES OF INTERNATIONAL TAX RELATIONS AT PRESENT STAGE - N. A. Poponova; T. I. Minina (Вестник университета)
The subject of the study is key trends in the development of international tax relations at the present stage. The purpose of the article is to investigate the impact of globalization on international tax relations. Approaches to international taxation in modern conditions are largely determined by changes in the financial transactions of transnational corporations and the tendency to move the tax base from high-tax-rate states to lower-tax ones, as well as by innovative changes that have increased the mobility of business. The paper pays the main attention to the urgent problems of international tax relations: firstly, these are measures to combat the outflow of profits to offshore companies and the cooperation of states in the exchange of financial and tax information, and secondly, the impact of the digital economy on international taxation, manifested, in particular, in expanding tax avoidance opportunities. The study considers approaches of states to taxation of cryptocurrencies and prospects of international cooperation in this area. The authors make conclusions about sharp decrease of the offshore companies role as an instrument of international tax optimization and the need to develop a mechanism for new digital business models taxation.